E-procurement Implementation as Reflection of Good Governance in North Lombok Regency - Ni Luh Tut Tri Ratnawati; I Made Yuda Suryawan (ID Solutions, 2021)
The impact of migration in the digital world does not escape the process of improvement in government bodies. The presence of E-Government provides better public services, the internal effectiveness of government organizations is increasing, and public access to information in a government environment is getting easier. Responding to the need for the realization of good governance and improving the quality of public services in North Lombok Regency, investment in the procurement of goods and services from manual to electronic which is called e-procurement is encouraged. E-Procurement is a form of innovation by the North Lombok Regency Government in realizing e-Government. This research was conducted at the electronic procurement service (LPSE) North Lombok Regency, West Nusa Tenggara Province (NTB). The method used in this research is descriptive qualitative research method. The informants in this study were LPSE apparatus of North Lombok Regency, vendors and users of goods and services. Data analysis conducted in this study was to analyse the results of observations, interviews, and documentation obtained from the study. Research results Optimizing e-procurement system services in the process of procuring goods and services for the sake of realizing good governance in North Lombok Regency is in accordance with applicable principles including effectiveness and efficiency principles, participant principles, transparency principles and accountability principles are properly implemented by LPSE North Lombok to achieve good governance. In addition to the above principles, there is also a theory put forward by Edward in realizing good governance including communication, this has been done well by North Lombok LPSE; Resources, this is regarding financial resources that have been done well but in terms of human resources it is still not optimal; Disposition, in this case, LPSE Lombok Utara has run well where the leadership, staff and vendors have the same vision and mission; Bureaucracy and structure, in this case LPSE Lombok Utara, has implemented a good structure for the division of tasks for each staff